Unit commitment using a new integer coded genetic algorithm - Amjady, Nima; Shirzadi, Ali (European transactions on electrical power, 2009)
This paper proposes a new Integer‐Coded Genetic Algorithm (ICGA) for the solution of the thermal unit commitment problem. The thermal generating units scheduling consists of the sequence of operation/reservation times of the generating units, which is coded into a sequence of alternating sign integer numbers in the proposed ICGA. The minimum up and down time constraints of the generating units are directly coded in the chromosome structure of the ICGA. The proposed ICGA has a new hybrid crossover composed of modified average bound and swapping operators. In addition, a combination of uniform and non‐uniform mutations is used as the mutation operator. As a result, the algorithm robustness is improved. Test results with systems of up to 300 units and 24 hours scheduling horizon are presented. The comparison of the obtained results with those of other Unit Commitment (UC) methods justifies the effectiveness of the proposed method in light of minimizing the total operation cost. Copyright © 2008 John Wiley & Sons, Ltd.